Relationship Between Low Birth Weight and Neonatal Jaundice: Retrospective Case-Control Study at Wates Regional Hospital - Sri Handayani; Emy Siti Lestari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Neonatal mortality is a critical indicator of public health and reflects the quality of maternal and neonatal healthcare services in a country. Low birth weight (LBW) and neonatal jaundice are among the leading causes of neonatal morbidity. This research aims to investigates the relationship between LBW and the incidence of neonatal jaundice in infants treated at the NICU of RSUD Wates, Kulon Progo, Yogyakarta. The findings will inform evidence-based policies and targeted interventions for Kulon Progo and surrounding areas. Methods: This quantitative analytical study employed a retrospective case-control design. Data were collected from medical records of neonates admitted at the NICU of RSUD Wates from January to April 2023. A total of 200 neonates were selected using purposive sampling based on the study's criteria. Data analysis was performed using SPSS 25, with chi-square tests to examine the relationship between LBW and neonatal jaundice. Results: The analysis revealed that 35% of infants were LBW, and 28% experienced neonatal jaundice. The chi-square test showed a significant association between LBW and neonatal jaundice, with a p-value of < 0.001. Infants with LBW were 4.15 times more likely to develop jaundice compared to those with normal birth weight. Conclusion: This condition is a major contributor to the development of neonatal jaundice, with a 4.15 fold increased risk. These findings highlight the importance of early detection and management of LBW to reduce the incidence of neonatal jaundice and improve neonatal outcomes, particularly in regions with high LBW prevalence.